Dampak Program Revitalisasi Pasar Terhadap Kesejahteraan Para Pedagang Di Pasar Pelita Kota Sukabumi - Wulandari Nur Utami; Ade Yunita Mafruhat (UNISBA Press, 2023)
Abstract. The existence of Sukabumi City’s market pelita has an important role ini the local economy. Over time, this market has faced various challenges, such as poor infrastructure conditions and a decrease in consumer attractivesness. The government has made efforts to improve the conditions and well-being of traders through market revitalization programs. Based on thes program, the study aims to understand the impact of traditional market revitalization programs on the well-being of traders in the Sukabumi City market pelita. This research uses quantitative methods with a descriptive analysis approach. The population in this study was made up of traders in the market pelita, with as many as 300 traders. Nonprobability Sampling with purposive sampling of 55 traders data collection techniques include field surveys, interviews, documentation, and qustionnaires. The analysis techniques in this study are instrument testing with the help of SPSS Software Version 26 and descriptive analysis. The result of data processing concluded that the revitalization program has a very positive impact on the well-being of traders in the Sukabumi City market pelita, with the presentation of respondents’ responses of 94,25% seen from the traders’ welfare indicators such as income, trader satisfaction, number of visitors, and physical facilities of the market. Abstrak. Keberadaan pasar pelita Kota Sukabumi memiliki peran penting dalam perekonomian lokal, seiring berjalannya waktu, pasar ini dihadapkan berbagai tantangan seperti kondisi infrastruktur yang buruk hingga penurunan daya tarik konsumen. Pemerintah mengeluarkan upaya untuk meningkatkan kondisi dan kesejahteraan pedagang melalui program revitalisasi pasar. Berdasarkan permasalahan tersebut, penelitian ini bertujuan untuk mengetahui dampak program revitalisasi pasar tradisional terhadap kesejahteraan para pedagang di pasar pelita Kota Sukabumi. Penelitian ini menggunakan metode kuantitatif dengan pendekatan analisis deskriptif. Populasi dalam penelitian ini adalah pedagang di pasar pelita sebanyak 300 pedagang. Dengan teknik pengambilan sampel menggunakan Nonprobability Sampling dengan teknik Purposive Sampling sebanyak 55 pedagang. Teknik pengumpulan data yang dilakukan dengan survei lapangan, wawancara, dokumentasi, dan kuesioner. Teknik analisis dalam penelitian ini adalah uji instrument dengan bantuan software SPSS Versi 26 dan analisis deskriptif . Hasil pengolahan data menyimpulkan bahwa program revitalisasi memiliki dampak yang sangat positif terhadap kesejahteraan pedagang di pasar pelita Kota Sukabumi dengan presentase jawaban responden sebesar 94,25% dilihat dari indikator kesejahteraan pedagang yakni pendapatan, kepuasan pedagang, jumlah pengunjung, dan fasilitas fisik pasar.